Evaluation of an educational conference for persons affected by hereditary frontotemporal degeneration and amyotrophic lateral sclerosis - Laynie Dratch; Weiyi Mu; Elisabeth McCarty Wood; Brianna Morgan; Lauren Massimo; Cynthia Clyburn; Tanya Bardakjian; Murray Grossman; David J. Irwin; Katheryn A.Q. Cousins (Elsevier, 2023)
Objective: There are limited studies exploring the support and education needs of individuals at-risk for or diagnosed with hereditary frontotemporal degeneration (FTD) and/or amyotrophic lateral sclerosis (ALS). This study evaluated a novel conference for this population to assess conference efficacy, probe how participants assessed relevant resources, and identify outstanding needs of persons at-risk/diagnosed. Methods: We implemented a post-conference electronic survey that probed participants' satisfaction, prior experience with resources, and unmet needs. Along with multiple-choice, free-text items were included to gather qualitative context. Results: Survey completion rate was 31% (115/376 attendees who were emailed the survey). There was positive interest in pursuing genetic counseling among eligible responders: 61% indicated they planned to seek genetic counseling because of the conference, which was significantly more than those who were undecided (21%) or did not plan to seek genetic counseling (18%). Qualitative data demonstrated need for additional education, support, and research opportunities. Conclusion: Conference reactions indicate this is a valued resource. Results indicated the importance of raising awareness about existing resources, and the need for further resource development, especially for at-risk communities. Innovation: While most resources are developed for caregivers' needs, this unique program targets at-risk individuals and unites ALS and FTD communities.